2020
DOI: 10.3389/fneur.2020.00475
|View full text |Cite
|
Sign up to set email alerts
|

Brain Proteomic Profiling in Intractable Epilepsy Caused by TSC1 Truncating Mutations: A Small Sample Study

Abstract: Tuberous sclerosis complex (TSC) is a genetic disease characterized by seizures, mental deficiency, and abnormalities of the skin, brain, kidney, heart, and lungs. TSC is inherited in an autosomal dominant manner and is caused by variations in either the TSC1 or TSC2 gene. TSC-related epilepsy (TRE) is the most prevalent and challenging clinical feature of TSC, and more than half of the patients have refractory epilepsy. In clinical practice, we found several patients of intractable epilepsy caused by TSC1 tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In summary, through the enrichment gene ontology analysis, the researchers found that DE proteins were mainly the components of synaptic membranes; the biological processes that were highly enriched were amino acid metabolism and the molecular functions related to antioxidant activity, ligase activity, and tetrapyrrole binding, which had an especially high number of DE proteins. Taken together, these data suggest that TSC mutations or alterations in patients’ synaptic proteins may affect the information transmission in the cells, and changes in patients’ amino acid metabolism can be a new mechanism to be explored in the TSC complex context (Liu et al, 2020 ).…”
Section: Proteomic Studies In Human Epilepsymentioning
confidence: 98%
See 4 more Smart Citations
“…In summary, through the enrichment gene ontology analysis, the researchers found that DE proteins were mainly the components of synaptic membranes; the biological processes that were highly enriched were amino acid metabolism and the molecular functions related to antioxidant activity, ligase activity, and tetrapyrrole binding, which had an especially high number of DE proteins. Taken together, these data suggest that TSC mutations or alterations in patients’ synaptic proteins may affect the information transmission in the cells, and changes in patients’ amino acid metabolism can be a new mechanism to be explored in the TSC complex context (Liu et al, 2020 ).…”
Section: Proteomic Studies In Human Epilepsymentioning
confidence: 98%
“…A very recent study (Liu et al, 2020 ) reported mutation analyses, clinical features, and tissue proteomic profiles of three patients with epilepsy caused by truncating TSC1 mutations. The authors used a DIA (Data-independent acquisition) workflow to explore the proteomic profile of these patients compared with control tissue from craniocerebral trauma surgery and found downregulation of ARFGEF2, which has been associated with intellectual disability and abnormal neuronal migration (Hong et al, 2018 ; Liu et al, 2020 ).…”
Section: Proteomic Studies In Human Epilepsymentioning
confidence: 99%
See 3 more Smart Citations